Remembering the 'Italian' Jewish homes of Libya: gender and transcultural memory (1967–2013). Issue 5 (20th October 2018) - Spadaro, Barbara
ABSTRACT: The article features memories of home and domestic culture of Jewish men and women displaced from Libya to Italy (the former colonial metropole), Israel and the UK after 1967. Adopting a transcultural perspective, the article exposes how ideas of Jewish, Italian and Arab culture and their gendered and racialized representations are negotiated by the interviewees. Developing an interdisciplinary method for the reading of six interviews, my aim is to offer two interrelated contributions. Firstly, to shed light on sites of transcultural experience marginalised by mainstream narratives of history, namely Jewish homes in Libya and Italy from the eve of the Italian occupation to the present. The article highlights in particular how these memories are conveyed through food and language. Secondly, by examining how memories of homes of the past emerge in the interviews, the article foregrounds the role of emotions, power and agency in contemporary mnemonic processes, stressing the gendering dimension of memory.